Sleep loss effects on physiological and cognitive responses to systemic environmental hypoxia - Fabries, Pierre; Gomez-Merino, Danielle; Sauvet, Fabien; Malgoyre, Alexandra; Koulmann, Nathalie; Chennaoui, Mounir (Frontiers in Physiology, 2022)
In the course of their missions or training, alpinists, but also mountain combat forces and mountain security services, aircrew, aircraft and glider pilots and helicopter crews are regularly exposed to altitude without oxygen supplementation. At altitude, humans are exposed to systemic environmental hypoxia induced by the decrease in barometric pressure (<1013 hPa) which decreases the partial pressure of oxygen (PpO2), while the oxygen fraction is constant (equal to approximately 20.9%). Effects of altitude on humans occur gradually and depend on the duration of exposure and the altitude level. From 1500 meters altitude (response threshold), several adaptive responses offset the effects of hypoxia, involving the respiratory and the cardiovascular systems, the oxygen-carrying capacity of the blood . Fatigue and cognitive and sensory disorders are usually observed from 2500 m (threshold of prolonged hypoxia) and, more gradually, some possible morphologic and functional adaptations in the skeletal muscle. Above 3500 m (the threshold of disorders), the effects are not completely compensated and maladaptive responses occur and individuals develop altitude headache or acute altitude illness (Acute Mountain Sickness (AMS)). The magnitude of effects varies considerably between the different physiological systems and show a large inter-individual variability. In addition to comorbidities, the factors of vulnerability are still little known. They can be constitutive (genetic) or circumstantial (sleep deprivation, fatigue, speed of ascent...). In particular, sleep loss, a condition that is often encountered in real-life settings, could have an impact on the physiological and cognitive responses to hypoxia. In this review we summarize the current state of human-based evidence on the impact of sleep loss on responses to environmental hypoxia with the objective to identify possible consequences on cognition and the AMS risk, and the interest of behavioral and nonpharmacological countermeasures.